Science verbs as a tool for investigating scientific phenomena – a pedagogical idea emerging from practitioner-researcher collaboration - Sofie Areljung (Nordina: Nordic Studies in Science Education, 2016)
This paper communicates the pedagogical idea of approaching scientific phenomena through verbs. The idea has sprung from a collaboration between preschool practitioners and a researcher, addressing science education in preschool (children aged 1-5 years). Drawing on a joint problem inventory, the project group aimed to create a teaching model that supports inquiry-oriented approaches to science, and teachers’ ability of distinguishing chemical processes and physics phenomena in everyday practice. The core idea of the teaching model turned out to be a list of everyday verbs, connected to scientific phenomena. Starting from verbs appear to help teachers to recognise the scientific phenomena in everyday practice. Further, the verbs guide the formulating of questions that can be answered by scientific inquiry, such as: ''what matters to how something melts/rolls/mixes?''.